2021
DOI: 10.4236/ojbm.2021.93063
|View full text |Cite
|
Sign up to set email alerts
|

Business Continuity Management in a Time of Crisis: Emerging Trends for Commercial Banks in Zimbabwe during and Post the Covid-19 Global Crisis

Abstract: Covid-19 has presented severe and increasingly complicated challenges which confront the very survival of banks in Zimbabwe. The urgency and relevance of business continuity management (BCM) to alleviate potential risks and quicken recovery remain important. While there is proliferation of literature on the impact of Covid-19 on businesses across the globe, there is little known about BCM strategies among Zimbabwean banks under Covid-19 conditions. This paper focuses on emerging trends in BCM approaches in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…As a class of IS-related financial service organizations, the banks have also suffered from a great deal of damages in the catastrophe. For instance, in Zimbabwe, many banks operating brick and mortar branches have been in trouble since the start of 2020 (Muparadzi, T., and Rodze, L., 2021) [12]. Moreover, regarding the First State Bank on Sohu (2020) [13], the Federal Deposit Insurance Corporation (FDIC) announced on 3 April 2020, that the First State Bank in West Virginia has closed down.…”
Section: Covid-19 Effects On the Banking Servicementioning
confidence: 99%
See 1 more Smart Citation
“…As a class of IS-related financial service organizations, the banks have also suffered from a great deal of damages in the catastrophe. For instance, in Zimbabwe, many banks operating brick and mortar branches have been in trouble since the start of 2020 (Muparadzi, T., and Rodze, L., 2021) [12]. Moreover, regarding the First State Bank on Sohu (2020) [13], the Federal Deposit Insurance Corporation (FDIC) announced on 3 April 2020, that the First State Bank in West Virginia has closed down.…”
Section: Covid-19 Effects On the Banking Servicementioning
confidence: 99%
“…Moreover, the essential elements of BCM are the components of organizational tactical management, the advance recognition of the potential threats, the early resilience establishment, the program and the review of the strategies to the consequences of the damage, as well as a risk managerial method (Muparadzi, T., and Rodze, L. 2021) [12]. Therefore, BCM's key factors' application and its effectiveness is crucial to the continuity and the sustainability of the organizations' business processes.…”
Section: Business Continuity Managementmentioning
confidence: 99%
“…As compared to SMEs, larger firms have a pre-established committee, consisting of senior members, who reinforce the whole BCM practice such as risk assessment, embedding efforts and continuity strategies. In contrast with SMEs, they have embedded the BCM as their part of organisational culture and not an ad hoc practice (Margherita and Heikkilä, 2021; Muparadzi and Rodze, 2021; Chen and Xu, 2022). Following the pandemic, they gather the lessons learnt and adjust the plan accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Kosieradzka et al, 2022;Riglietti et al, 2022). There are a few studies that focused on large companies (Margherita and Heikkil€ a, 2021;Muparadzi and Rodze, 2021). They found that large companies had developed an immediate response to ensure the continuity of their business operations.…”
Section: Business Continuity Management Principlesmentioning
confidence: 99%
“…Awareness and training provide the required confidence to internal and external stakeholders for the organization's disaster recovery ability (Khanna, 2008). The entire staff of the organization from rank and file employees to the executive must be conscious of their expected roles and responsibilities in reaction to disaster recovery efforts to avert palpable resource waste (Muparadzi & Rodze, 2021). In a Malaysian study, Abdullah, Noor and Ibrahim (2015) showed that people/employees factor is significantly and positively correlated with BCM implementation in the Public Sector.…”
Section: Relationship Between Critical Personnel/employees and Bcmmentioning
confidence: 99%